Comparative analysis of photovoltaic technologies for high efficiency solar cell design - Sharma, Divya; Mehra, Rajesh; Raj, Balwinder (Superlattices and microstructures, 2021)
Sun is the provenance of all kinds of energy prevailing on earth since ages. Being renewable and pollution free, solar energy has paved the way to compensate the exploitation of non-renewable sources of energy through the discovery of solar/photovoltaic cells. Considerable developments have been witnessed in solar cells with the passage of time which not only resulted in their compact sizes but also resulted in increased power conversion rate. This paper presents comparative analysis of photovoltaic through a detailed study of constructions, applications and efficiencies of the solar cells of third generation including their future trends and aspects. Among all types of solar cells, till date concentrated solar cells have shown maximum efficiency of 38.9%. •Being renewable and pollution free, solar energy has paved the way to compensate the exploitation of non-renewable sources of energy through discovery of solar cells.•Developments have been witnessed in solar cells with the passage of time which not only resulted in their compact sizes but also resulted in increased power conversion rate.•This paper presents detailed study of constructions, applications and efficiencies of the solar cells of third generation including their future trends and aspects.•Among all types of solar cells, till date concentrated solar cells have shown maximum efficiency of 38.9%.